Decolorisation treatments of azo dye waste waters including dichlorotriazinyl reactive groups by using advanced oxidation method - UYGUR, AYŞE; KÖK YETİMOĞLU, ECE (Society of Dyers and Colourists, 1999)
Decolorisation treatments of azo dye waste waters, which include dichlorotriazinyl reactive groups, were investigated by using ultraviolet (UV) radiation and hydrogen peroxide at various exposure times. Decolorisation time decreased when UV radiation power and hydrogen peroxide concentration increased. Colour removal reached 98.0-99.5% by using this method. Some environmental parameters of decolorised waste water, such as biological oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC), total inorganic carbon (TIC), total carbon (TC), adsorbable organohalides (AOX), sulphate and chloride, were determined. It was concluded that TOC, COD and AOX decreased while BOD increased and sulphate ions remained unchanged. These results suggested that the dye molecules were totally destroyed and some of these decomposition products were removed as carbon dioxide and water to some degree.